2022
DOI: 10.2214/ajr.21.26274
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Safety of Contrast-Enhanced Ultrasound of the Neonatal Brain: A Prospective Study Using MRI as the Reference Standard

Abstract: The publication of this Accepted Manuscript is provided to give early visibility to the contents of the article, which will undergo additional copyediting, typesetting, and review before it is published in its final form. During the production process, errors may be discovered that could affect the content of the Accepted Manuscript. All legal disclaimers that apply to the journal pertain. The reader is cautioned to consult the definitive version of record before relying on the contents of this document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…The risk of hypoxic-ischemic injury, intraventricular hemorrhage, PVL, and hemorrhagic hydrocephalus is significantly higher in preterm infants, which is an important tool for diagnosis and monitoring of brain injury in preterm infants. Therefore, studies have used MRI as the reference standard to evaluate the feasibility, safety, and diagnostic value of transfontanel cerebral CEUS in newborns ( 31 , 32 ). As shown in Figure 6D , the top 20 keywords that appear most frequently have new research directions in different stages with the deepening of the research, and their influence and research activity deserve attention.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of hypoxic-ischemic injury, intraventricular hemorrhage, PVL, and hemorrhagic hydrocephalus is significantly higher in preterm infants, which is an important tool for diagnosis and monitoring of brain injury in preterm infants. Therefore, studies have used MRI as the reference standard to evaluate the feasibility, safety, and diagnostic value of transfontanel cerebral CEUS in newborns ( 31 , 32 ). As shown in Figure 6D , the top 20 keywords that appear most frequently have new research directions in different stages with the deepening of the research, and their influence and research activity deserve attention.…”
Section: Discussionmentioning
confidence: 99%
“…Distinguish complex from simple ovarian cysts. Distinguish gallbladder inspissated bile (tumefactive sludge) from vascularized soft tissue that may indicate neoplasm or focal adenomyomatosis 10 Improve diagnostic performance of US in infant brain evaluation 19,20 Evaluate neonatal brain hypoxic ischemic injury 21 …”
Section: Indicationsmentioning
confidence: 99%
“…Imaging should be performed continuously from contrast injection until the imaging target is adequately characterized. Presence and degree of arterial phase enhancement should be documented. Neonatal brain 19–21,33 Contrast dose: CEUS examination of the neonatal brain is performed using the standard pediatric weight‐based dose of 0.03 mL/kg SHLM contrast. Imaging: CEUS examination of the neonatal brain is performed with a small footprint curved‐array mid‐frequency transducer. CEUS is performed by saving cinematic clips. Once SHLM has been injected, care must be taken to only image in low mechanical index (MI), low TI, and low power output mode to avoid microbubble destruction and potential sonoporation. High MI pulses to clear the field should not be used. First, a wash‐in cinematic clip is obtained in the coronal plane at the level of the third ventricle for 30 seconds after contrast injection 20 …”
Section: Specification Of the Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…CEUSs have been used for the evaluation of acute ischemic stroke among an adult population to detect cerebral perfusion deficits and to monitor the responses to a thrombolytic treatment [ 49 , 50 ]. The number of studies on a pediatric population, so far, are minimal, but CEUSs have been shown to have good sensitivity to detect acute ischemic stroke in comparison to MRI [ 51 ]. For the imaging of stroke using CEUS, the quantitative brain perfusion analysis is typically performed.…”
Section: Clinical Applicationsmentioning
confidence: 99%